Pembuatan Program Perataan Parameter Jaring Poligon Dengan Menggunakan Visual Basic For Application (VBA) Microsoft Excel - Eva Suci Lestari; L. M. Sabri; Bambang Darmo Yuwono (Jurnal Geodesi UNDIP, 2014)
Least square method is one method most popular to problem-solving count flattening. The ordinal least quadrat in cases of the count of geodesy which simple, e.g. cutting measurement of angles, levelling and measurement of distances the base. A traverse do the count based on error angle of a polygon and distance results size reference to the terms of geometric polygons measured. Within adjustment required leveling high Count in the process of calculation. Therefore, the required computer technology  in the process of doing the calculation so that the result is more precision. With the progress of the current process of computer calculations can be done quickly through programming. Program used as thesis harnesses Program macros with visual basic for application (VBA) programming language in microsoft Excel by using the polygon mesh data.Keyword : Least square method , Macro or VBA, Ms. Excel